Gender Disparities in the Use of ICT: A Survey of Students in Urban Schools - Basavaraja, M.T.; Sampath Kumar, B.T. (Journal of Information Science Theory and Practice, 2017)
This study aims to investigate gender differences in the use of ICT by the students of urban schools. The objectives of the study are to find out the use of computers and Internet by the students and also the problems encountered by them while using computers and Internet. The study found that there is a significant association between the place (p=.005) and frequency (p=.002) of use of computers and gender. It is also found that there are significant differences in the problems faced by students while using computers (p=.002), use of Internet (p=.004), and the gender. This clearly indicates that there exists a gender disparity in the use of ICT by the male and female students in the urban schools. In order to overcome this disparity, the school authority should provide the basic and necessary ICT infrastructure in schools which can be equally used by male and female students.